Are Persons with disabilities happy? : The Effects of Poverty and Gender on Happiness - Ok Kim, Mi; Kyung Nho, Si; Young Jeong, Jun (International Journal of Psychosocial Rehabilitation, 2019)
We ask in this study “Are Persons with disabilities happyindeed?” and perform a comparative analysis of the factors that affect happiness according to poverty and gender. To this end, this study used the third survey(2018) data from the Second-Wave Panel Survey of Employment for the Disabled and analyzed data on 3,778 disabled person aged 20 or older. Groups were classified into four groups of no-poverty males with disability, nopoverty females with disability, males with disability suffering poverty, and females with disability suffering poverty.Descriptive statistical analysis shows that happiness, health status, household income, housing satisfaction, interpersonal relationships, and self-esteem are all above median values, that the level of participation in social activities is around average, and that socioeconomic status and discrimination experience are below average. Comparative analysis of differences of groups shows that there exist statistically significant differences for all the major variables among all groups. Multi-regression analysis confirms that health status, socioeconomic status, housing satisfaction, and self-esteem are factors that affect the happiness of all groups. It is also confirmed that chronic diseases and interpersonal relationships are statistically significant only among groups of the disabled in non-poverty, that employment is statistically significant among disabled males in non-poverty only, that participation in social activities has a statistically significant effect among the group of disabled males in nonpoverty and the group of disabled females in poverty, and that experiencing discrimination has a statistically significant negative effect on happiness among disabled females only. The study suggests that providing the disabled with customized supports that take different characteristics of disability into consideration is required. Further, the implementation of the pertinent welfare system and institutional support according to poverty and gender for the disabled is also suggested.